Influence of the Addition of Vitamin E in Extenders in the Quality of Fresh Semen Diluted, Refrigerated and Frozen Semen in Dogs of French Bulldog Breed - Chacur, Marcelo George Mungai; Souza, Mariana Grandis Ripari de; Souza, Camila Dutra de; Cremasco, Camila Pires (Acta Scientiae Veterinariae, 2017)
Background: Researches have been conducted in order to maintain the quality of the fresh semen which is diluted, refrigerated or frozen in liquid nitrogen for artificial insemination purposes in dogs. The semen biotechnology cooperates with the development of new formulations of types of extenders which minimize the death of the sperms due to thermal stress during temperature reduction of the refrigeration and freezing curves of the semen. The objective was to study the influence of the addition of vitamin E in types of extenders in the quality of the fresh, refrigerated and frozen semen in dogs of French Bulldog breed. Materials, Methods & Results: Semen samples by digital manipulation were performed on 5 adult dogs, French bulldog breed, five on each dog, totaling 25 ejaculated. The characteristics evaluated in fresh semen were: Volume (mL), color, aspect, concentration (x106/mL), sperm motility (%), vigor (1-5) and sperm morphology (%). For refrigerated and frozen semen, motility (%), vigor (1-5) and morphology (%) were analyzed. The ejaculated ones were fractionated in 4 equal parts and diluted in the ratio 1: 1 in the following extenders: 1 – TRIS - Fructose Citric acid + 200 mM of vitamin E; 2 – TRIS - Fructose Citric acid; 3 - coconut water (ACP-106®) + 200 mM of vitamin E; and 4 – coconut water (ACP-106®). The four aliquots of semen, diluted in the four respective extenders were centrifuged at 1500 g/10 min and the “pellets” formed of sperm from every ejaculated, detached from the tubes wall were diluted homogeneously with the four extenders to the volume of 1.5 mL and filled into 0.5 mL French straws kept under refrigeration at 5oC/4 h after placed in a nitrogen vapor at -120ºC/15 min, and immersed in liquid nitrogen at -196ºC in the sequence stored in identified racks and stored in liquid nitrogen container until the time of thawing in a water bath at 37ºC/30 s for microscopic semen analysis. Data from fresh, refrigerated and frozen semen were statistically analyzed by analysis of variance and the average compared by Tukey (P < 0.05). For fresh semen diluted in the four extenders, in pre-cooling curve, there was a significant difference (P < 0.05) for defects in the sperm head, between TRIS + vit. E (7.59 ± 4.01%) and TRIS (10.48 ± 5.42%). In the post-cooling curve to 5ºC/4 h, for the four extenders, there was no difference (P > 0.05) between the evaluated characteristics. For frozen semen with TRIS and thawed at 37ºC/30 s, there was difference (P < 0.05) for the major sperm defects, being the top average (26.62 ± 5.52%) compared to the other three extenders. For minor sperm defects in frozen semen with TRIS, there was difference (P < 0.05) with a lower percentage of incidence (16.23 ± 2.02%) compared to other extenders. There was difference (P < 0.05) with a significant increase of total defects in frozen semen with the extender ACP + vit. E, compared to other extenders. Discussion: Attention should be paid for what purpose the extenders within the refrigeration or freezing biotech will be used. In the present study, we found that the microscopic analysis of the spermatic motility and vigor in frozen semen with the ACP extender is hampered due to the lower transparency of this extender in relation to the TRIS extender. We conclude that the TRIS + vit. E extender it is the most recommended to dilute the fresh semen for the purpose of immediate artificial insemination due to lower presence of the sperm head defects. For refrigeration, the four extenders are recommended, with similarity in semen characteristics maintenance. For frozen semen the indicated extenders are the TRIS, TRIS + vit. E, and the extender ACP. The addition of vit. E in these extenders did not provide improvement of refrigerated and frozen semen, with optional use of it.